Pengembangan lembar kerja peserta didik berbasis pendekatan saintifik pada pembelajaran IPA kelas V DI SD Negeri Tegalpanggung Yogyakarta - Tessa, Namira Chyka; Utaminingsih, Retno (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This research aims to: 1) develop LKPD based on a scientific approach in science learning in grade V of elementary school; 2) to determine the feasibility of LKPD based on a scientific approach in science learning in grade V of elementary school by material experts, media experts, and class teachers; 3) to determine students' responses to LKPD based on a scientific approach in science learning in grade V of elementary school. This study is a Research and Development (R&D) study with the ADDIE development model consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques use unstructured interview techniques, observation, and questionnaires in the form of a multilevel/likert scale. Data analysis techniques use qualitative data analysis and quantitative data analysis. The feasibility of the media is obtained from the validation results carried out by material experts, media experts, and class teachers using instruments in the form of validation questionnaires, and students using instruments in the form of response questionnaires. The results of the study indicate that 1) the study produced a LKPD product based on a scientific approach in science learning for grade V elementary schools with a focus on the material on the "Water Cycle"; 2) the LKPD product based on a scientific approach is very feasible to use in the learning process based on the results of the validation of material experts obtained a percentage score of 92.8%, the results of the validation of media experts obtained a percentage score of 89.7% and the results of the validation of class teachers obtained a percentage score of 94%; 3) the LKPD product based on a scientific approach in science learning received a positive response from students based on the results of student responses obtained a score of 89,4%. Based on the results of the feasibility of material experts, media experts, and class teachers as well as student responses, the scientific-based LKPD product in science learning in grade V of Tegalpanggung State Elementary School was declared very feasible to be used in the learning process. LKPD based on a scientific approach can be used as an alternative learning tool for teachers and a learning reference for students in science learning on the water cycle material.